Une Fonction de production des billes de merisier au Canada - Carpentier, Gilles N (University of Ottawa (Canada), 1972)
Abstract not available.
Keywords: Agriculture, Forestry and Wildlife.; Engineering, Industrial.; Agriculture, Wood Technology.